Sensores acústicos distribuídos para análise sísmica - Silveira, Erik Tarlles (2023)
Distributed Acoustic Sensing - DAS - represents a new frontier in advancing fiber optic sensors, constituting a sensing modality that turns the whole length of a fiber optic cable into a sensing element, a favorable condition to be applied in seismic studies. With the aim of better understanding the application and opportunities offered by such technology applied in seismic sensing, this work presents two studies: a theoretical comparison between the main characteristics of the conventional technique, based on geophones, and the distributed sensing; and another practical one, where data acquired with Distributed Acoustic Sensors were processed, with the application of concepts and techniques adopted in seismic surveys, to identify geological features that are of interest in the prospection for oil and natural gas, such as the individualization of rock formations. The theoretical study shows the rapid development of technology and its adoption for geological investigations through the seismic method. It also points out some opportunities for improvement in the application of the method and for disseminating technology in the academic environment. Although a complete processing cycle was not fished in the practical study, it was possible to establish a correlation between the data obtained and the area’s stratigraphy with the individualization of two geological formations.